An inertial piezoelectric actuator with miniaturized structure and improved load capacity. (15th April 2019) - Shao, Yan; Shao, Shubao; Xu, Minglong; Song, Siyang; Tian, Zheng
Abstract: An inertial actuator that improves load capacity within a miniaturized structure has drawn wide attention. This work proposes an inertial piezoelectric linear actuator and investigates a method that improves its load capacity. The structure and operational principle of the actuator are introduced. A dynamic model of the system is established that simulates the stepping characteristics. The dominant parameters affecting load capacity are discussed in detail. A prototype was manufactured and its main performance features tested. The experimental results confirm that the proposed actuator achieves a load capacity of 3.65 N, a resolution of 0.47 μ m, and a speed of 6.15 mm s −1, despite its compact size of Φ 9 mm × 27 mm. The actuator has an improved load capacity given its smaller configuration than those reported in the literature. The model established provides a theoretical guide to the design of similar inertial actuators and may be used to predict and evaluate their load capacity.